Improving medical students’ confidence with supplemental training programs: a medical student’s view - Maleki A; Patel CR (Advances in Medical Education and Practice, 2017)
Aryan Maleki, Chandni Rajesh PatelFaculty of Medicine, Barts and The London School of Medicine and Dentistry, London, UKWe read with great interest the article by Fazel et al evaluating the effectiveness of supplemental diabetes-specific educational programs at increasing medical students’ confidence when discussing diabetes self-management education and support with patients.1 As medical students who have just finished pre-clinical years, we are at the stage where confidence issues regarding patient communication are high. With an aging population and the prevalence of patients with multiple co-morbidities increasing, the landscape of modern medicine is shifting to a more community-based approach. It is becoming more important to educate patients on self-management and deliver health promotion strategies, while incorporating the whole multidisciplinary team in their treatment.View the original paper by Fazel and colleagues.